SAT0215 Characteristics of patients with ankylosing spondylitis, rheumatoid and psoriatic arthritis in treatment with biologics in verona's cohort: results from veneto's region biologics register. (15th June 2017) - Troplini, S; Viapiana, O; Fracassi, E; Carletto, A; Idolazzi, L; Orsolini, G; Giollo, A; Rossini, M
Abstract : Background: Since 2013, in Veneto's Region, data registration is mandatory for all patients affected by Rheumatoid arthritis (RA), Psoriatic Arthritis (PA), Ankylosing Spondylitis (AS) in treatment with biologic agents. The biologic DMARDs currently marketed in Italy are: anti-TNF (originator and biosimilar infliximab, etanercept, adalimumab, certolizumab and golimumab), anti-IL6 (tocilizumab), anti-CD20 (rituximab), CTLA-4 like (abatacept) and anti IL-12/23 (ustekinumab). Objectives: The aim of this study was first to describe the characteristics of patients with RA, PA, AS under biologics and then, to extract and analyze real-life data regarding rheumatic treatments in Verona's cohort. Methods: The study has been carried out on behalf of Regione del Veneto, Giunta regionale- Ricerca Sanitaria Finalizzata-Venezia-Italy. Data used for analysis were retrieved from Veneto's Region Biologics Register (VRBR). VRBR provides that core variables such as onset and type of disease, anthropometric characteristics (age, sex, body weight, height) are registered at the beginning. Furthermore, prior and concomitant rheumatic treatment (conventional and biologic DMARDs, corticosteroids, NSAIDs), disease activity indicators (DAS 28-PCR, ASDAS-PCR, pain-NRS), prognostic factors (positivity for rheumatoid factor and/ or anti-citrulline antibodies in AR, presence of radiological erosions) were assembled at baseline, every 6 months and at the time of biologic's switch or swap. Results: A total of 983 patients under biologics were examined; 543 (55, 2%) with AR, 272 (27, 7%) with AP and 168 (17, 1%). Between these, 262 (27, 2%) patients were naïve to biologics, 128 with AR, 84 with AP, 50 with SA. Mean duration of disease was of 15, 3, 10, 7 and 12, 6 years respectively for RA, PA and AS. Radiological erosions were present in 73% of RA-patients and the percentage was higher in those with positivity for rheumatoid factor and/ or anti-citrulline antibodies (84, 4% versus 56, 2%). More than half of the patients in this cohort were treated at least with one biologic agent; anti-TNFs were the main biologic used (RA:54, 8%, PA:92, 7%, AS: 100%) followed by Abatacept (25, 4%), tocilizumab (12, 3%) and rituximab (5, 9%) in patients with RA. Methotrexate (MTX) was the prevalent associated c-DMARDs (41, 8% in RA and 34, 2% in PA) with mean dose of 11, 9 mg/week in RA and 12, 1 mg/week in PA. The optimal dose of methotrexate was not achieved prevalently because of drug intolerance. Conclusions: Profile of both conventional and biological DMARDs looks very different according to the type of rheumatic disease. The first data show an underuse of MTX in patients with RA and PA under biologics with a low mean dosage due to intolerance. Next step is to evaluate long-term outcomes in clinical practice. Disclosure of Interest: None declared